The Ethical and Social Impact of AI Technologies Like ChatGPT - Chougule, Ashwini T; Harke, Supriya S; Mente, Rajivkumar S; Chendage, Bapu D (International Journal of Computer Sciences and Engineering, 2025)
AI models like ChatGPT are changing how as the users communicate, learn, receive healthcare, and enjoy entertainment. Artificial Intelligence (AI) is transforming industries like healthcare, smart homes, retail, self-driving cars, and financial fraud detection. While AI improves efficiency and automates tasks, it also raises major ethical and social concerns. Some of the biggest issues include data privacy, misinformation, bias in decision-making, job loss, security risks, and difficulties in regulating AI. This paper takes a closer look at these concerns and explores ways to make AI more responsible, fair, and transparent while ensuring it benefits society.